Mindful Parenting sebagai Strategi Pengasuhan Anak dalam Menghadapi Stres Keluarga - Napisah Napisah; Halimatus Sakdiah (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to examine mindful parenting as a parenting strategy in addressing family stress through a qualitative descriptive approach using library research. The increasing complexity of modern family life, including work demands, dual-earner roles, economic pressure, and emotional challenges in childrearing, has heightened parenting stress and affected the quality of parent–child interactions. Mindful parenting emphasizes present-moment awareness, emotional regulation, and non-judgmental acceptance in parenting practices, enabling parents to respond more adaptively to stressful situations. The findings from previous studies indicate that mindful parenting contributes to reducing parenting stress, enhancing parental emotional stability, and fostering positive parent–child relationships across diverse family contexts, including families with young children, working parents, and parents of children with special needs. Furthermore, mindful parenting supports children’s emotional regulation by modeling calm and reflective responses within the family environment. The synthesis of empirical evidence suggests that mindful parenting functions not only as an individual coping strategy but also as a sustainable approach to strengthening family resilience. Therefore, mindful parenting holds significant potential as a core framework for promoting healthy parenting practices and psychological well-being within contemporary families